METODE, TEKNIK, DAN INSTRUMEN PENILAIAN HASIL BELAJAR MATEMATIKA - Nasution, Mariam (IAIN PADANGSIDIMPUAN, 2017)
Every educator and learner is always curious about the outcame of the learning process in the classroom. To find out the results of the learning process educators need to conduct assessment of learning outcomesÂ and learning fraud. Assessment of the results of mathematic learning emphasizes to obtain information about how the acquisition of learners of mathematics learning is a systematic process to obain information about the effectivenees of the learning process in helping learners in achieving optimal learning objectives. Please noteÂ that in the process of assessment of learning outcomes of learners in learing mathematics required methods or techniquis and instruments that need to be considered and prepared, so that later learning objectives can be achieved. Techniquis and instruments used this will provide information to teachers on the circumstance and achievements achieved by learners. Teachersâ€™ learning techniquis and assessment instruments the can be developed by teachers can include assessment of test types, non-tests, grade-based assessments, performance appraisals, as well as portfolio assessments. Therefor, techniquis, methods, and assessment instruments that can be done by the teacher in evaluating the students. As a teacher will be required not only able to make an instrument of assessment of learning outcomes of learners, but able to apply and use the assessment instrument